Electrical properties and ultrafast photo-response of InGaAs/InP grown by low-temperature molecular beam epitaxy with a GaAs decomposition source - Kim, JM; Lee, YT; Song, JD; Kim, JH (ELSEVIER SCIENCE BV, 2004)
Lattice-matched InGaAs on (100) InP was grown by molecular beam epitaxy with arsenic dimers (As) at a growth temperature (T.) range of 250-470degreesC. Measurements of double-crystal X-ray diffraction reveal that Deltaa perpendicular to /a(o) of low-temperature-grown (LTG) InGaAs increases from 0.82 x 10(-2) (T-g = 470degreesC) to 4.1 x 10(-2) (T-g = 250degreesC) as T-g decreases. The measurements also indicate that excess arsenics are easily incorporated as antisites. All grown samples show a clear crystalline structure and are strong n-type. When T-g is decreased from 470degreesC to 250degreesC, then according to the Hall measurement the carrier concentration increases from 5.0 x 10(-16) to 2.4 x 10(-18) cm(-3) and according to the time-resolved reflectivity measurement the carrier lifetime decreases from 14.02 to 2.33 ps. Finally, for InGaAs/InP grown at 250degreesC, the incorporation of Be decreases the carrier lifetime to 1.86 ps and the residual n-type carrier concentration to 5.0 x 10(-16) cm(-3). Crystallized InGaAs/lnP with LTG material properties was obtained with a smaller V/III ratio and at higher growth temperature, compared to those with As-4. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: INTERACTION KINETICS; QUANTUM-WELLS; SURFACES